ADOLESCENT REPRODUCTIVE HEALTH CAMPAIGN ON SOCIAL MEDIA - Edi Santoso; Wiwik Novianti; Tri Nugroho Adi; Petrus Imam Prawoto Jati; Sri Pangestuti (Kinesik, 2022)
Social media plays an important role in today's adolescent reproductive health campaigns. This media is the media most used by teenagers. Its interactive and attractive characteristics match the youth's soul. This article explores how reproductive health campaigns are carried out on social media, especially YouTube, Instagram, and TikTok. The main focus is (1) Who are the actors involved in the youth reproductive health campaign and (2) what is the message content of the campaign. The research was conducted using descriptive qualitative methods, with a pragmatic approach. The data was extracted using qualitative content analysis techniques, which were then analysed in a narrative manner. The research findings show that message producers are both individuals and institutions. Individual message creators consist of influencers and health practitioners. The institutions that take part are educational institutions, hospitals or health centres’, non-governmental organizations, the health community, and the BKKBN. The campaign messages take various forms, following the social media platforms. Most of the campaigns on YouTube are carried out by institutions that display long videos containing education and consultation on reproductive and sexuality issues, as well as coverage of related events. The campaign on Instagram is also dominated by the institute, with messages in the form of photos and short videos. While on TikTok, campaigns are mostly carried out by individuals or influencers, with more attractive messages. Messages in the form of short videos on TikTok have received wide attention from netizens, which is reflected in the large number of related video views. In TikTok, sensitive messages such as sex before marriage are conveyed.